Rice body synovitis in pediatrics: three different case reports - Wang, Liping; Jin, Yingying; Huang, Hua; Yang, Zhen; Ding, Fei; Xu, Xuemei; Liu, Chenxi; Bao, Shengfang; Han, Xiqiong; Ma, Jing; Jin, Yanliang; Cai, Haiqing (Frontiers in Pediatrics, 2024)
Rice body synovitis (RBS) is a rare disease, especially in children. Rheumatoid disorders and tuberculosis are the first two reasons for the formation of the RB. The diagnosis is mainly based on imaging and histopathological features. Herein, we report three cases of RBS in children diagnosed with congenital synovial chondromatosis, tuberculosis (unconfirmed), and ANA -positive juvenile idiopathic arthritis. Clinical features, radiographic findings, pathophysiology, treatment process, and prognosis were reviewed and documented meticulously to enhance cognition in this population and provide some references for clinicians in diagnosing and treating the disease.